Study Effectiveness Web Site E-Commerce and Marketplace in Increasing Consumer Trust in Indonesian Retail Food Industry - Reza, Bobby; Sukartono, Sri; Azis, Nur; Irwansyah, Novi (ExcelingTech, 2020)
The presence of computers and the internet has now changed the face of human civilization, ranging from industry, education, to economics and commerce. One of the best-known things now is online transactions using the internet is an E-Commerce web site and marketplace. Retail companies are competing to market their products via the internet. It is quite interesting to analyze the issue of the extent to which the effectiveness of E-commerce Web sites and marketplaces in gaining consumer trust in the real food industry. More effective way to gain consumer trust. This study aims to determine the factors that influence consumer trust and buying interest in retail food products. The data in this study came from all consumers who had sold retail food products online throughout Indonesia. The results of the study indicate that the use of e-commerce and Marketplace web sites has its respective advantages and disadvantages to gain consumer trust in the retail food industry.